LncRNA FAISL Inhibits Calpain 2‐Mediated Proteolysis of FAK to Promote Progression and Metastasis of Triple Negative Breast Cancer - Yunmei Zhang; Shiyu Wei; Zhengjie Chen; Rui Xu; Shu‐Rong Li; Lili You; Ruiyue Wu; Yin Zhang; Jian‐You Liao; Xiaoding Xu; Erwei Song; Man‐Li Luo (Advanced Science)
Abstract Triple negative breast cancer (TNBC) is the most aggressive subtype in breast tumors. When re‐analyzing TCGA breast cancer dataset, we found cell adhesion molecules are highly enriched in differentially expressed genes in TNBC samples, among which Focal Adhesion Kinase (FAK) is most significantly associated with poor survival of TNBC patients. FAK is precisely modulated in the focal adhesion dynamics. To investigate whether lncRNAs regulate FAK signaling, we performed RNA immunoprecipitation sequencing and found FAISL (FAK Interacting and Stabilizing LncRNA) abundantly enriched in FAK‐interacting lncRNAs and frequently overexpressed in TCGA TNBC tissues. FAISL promotes TNBC cell adhesion, cytoskeleton spreading, proliferation, and anchor‐independent survival. FAISL doesn't affect FAK mRNA but positively regulates FAK protein level by blocking Calpain 2‐mediated proteolysis. FAISL interacts with the C‐terminus domain of FAK, whereby masks the binding site of Calpain 2 and prevents FAK cleavage. High level of FAISL correlates with FAK expression in tumor tissues and poor prognosis of TNBC patients. A siRNA delivery system targeting FAISL using reduction‐responsive nanoparticles effectively inhibits tumor growth and metastasis in TNBC mouse models. Together, these findings uncover a lncRNA‐mediated mechanism of regulating FAK proteolysis in the TNBC progression, and highlight the potential of targeting lncRNA FAISL for TNBC treatment.